Ozone therapy in pressure injuries as na alternative to nursig care (Research, Society and Development, 2021)
Currently, ozone therapy has been a practice of worldwide interest. It is an alternative in the treatment of pressure injuries given its antioxidant and bactericidal effects that directly influence biochemical factors of metabolism and cell regeneration. In Brazil, this practice is part of the National Policy for Integrative and Complementary Practices in Health, of the Unified Health System, through Ordinance No. 702 of March 21, 2018 from the Ministry of Health. The objective of this study is to identify the methods for use ozone therapy in the treatment with Pressure Injury (LPP) and describe the benefits of using ozone therapy in the treatment with pressure injury by nursing care. This is a bibliographic review based on national and international articles, with electronic scientific research such as: Virtual Health Library (VHL), Scielo and Google Scholar, as Brazilian technical- scientific references in nursing. And the results found indicate the importance of using this practice as an assistance option with      obtaining excellent rates of improvement.